1998
DOI: 10.1021/la980547f
|View full text |Cite
|
Sign up to set email alerts
|

S-Layer Reconstitution at Phospholipid Monolayers

Abstract: The recrystallization of the S-layer protein from Bacillus coagulans E38-66 at different lipid surface monolayer films has been observed to depend on (i) the nature of the lipid headgroup, (ii) the phase state of the surface monolayer, (iii) the ionic content, and (iv) the pH of the subphase. S-layer lattices formed at such interfaces were studied by electron microscopy and their orientation with respect to the lipid films was determined from the handedness of the base vectors defining the oblique crystal latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…In addition, TEM images have revealed an extremely bloated periplasm containing layers, possibly of membranous origin, to which the S-layer proteins were attached. There are several reports describing the interaction of Slayer proteins with lipid membranes (Schuster et al, 2008;Wetzer et al, 1998;Weygand et al, 1999) and lipidic vesicles can be stabilized by coating with S-layer proteins (Schuster et al, 2008). In the context of the high resistance of the tubes against SDS, guanidine hydrochloride, urea and ultrasonic treatment, the above-mentioned work supports the theory that the S-layer protein has a stabilizing effect on the excessively produced outermembrane-like structures in the filaments of the sllBexpressing E. coli strain formed in the early growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TEM images have revealed an extremely bloated periplasm containing layers, possibly of membranous origin, to which the S-layer proteins were attached. There are several reports describing the interaction of Slayer proteins with lipid membranes (Schuster et al, 2008;Wetzer et al, 1998;Weygand et al, 1999) and lipidic vesicles can be stabilized by coating with S-layer proteins (Schuster et al, 2008). In the context of the high resistance of the tubes against SDS, guanidine hydrochloride, urea and ultrasonic treatment, the above-mentioned work supports the theory that the S-layer protein has a stabilizing effect on the excessively produced outermembrane-like structures in the filaments of the sllBexpressing E. coli strain formed in the early growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of S-layer lattices covering the entire area of lipid films has been observed on zwitterionic phospholipids like PCs and in particular PEs [122]. S-layer proteins did not form crystalline lattices on negatively charged phospholipids.…”
Section: Free-standing Membranesmentioning
confidence: 96%
“…Electrostatic interaction is thought to exist between exposed carboxyl groups on the S-layer lattice and zwitterionic lipid head groups. At least two or three contact points between the S-layer protein and the attached lipid film have been identified [122]. Hence, less than 5% of the lipid molecules of the adjacent monolayer are anchored to these contact points (protein domains) on the S-layer protein whereas the remaining 95% or more of lipid molecules may diffuse freely within the membrane between the pillars consisting of anchored lipid molecules [120,187].…”
Section: Free-standing Membranesmentioning
confidence: 99%
“…[36], Copyright (2004), with permission from Wiley-VCH. One of the most important properties of S-layer proteins lies in their capability to reassemble into crystalline arrays in suspension [22,50], at interfaces such as porous or solid supports [51][52][53], the air-water interface [40,54], planar lipid films [40,[54][55][56][57][58] (Fig. (3)), on liposomes [59][60][61], and on nanocapsules composed of polyelectrolytes [62].…”
Section: Properties Of Crystalline Bacterial Cell Surface Layersmentioning
confidence: 99%
“…From this observation it has been concluded that electrostatic interactions between exposed carboxyl groups on the inner face of the S-layer lattice and the zwitterionic lipid head groups are primarily responsible for the defined orientation of the subunits. For such an alignment, it has been suggested that there are at least two to three contact points between the lipid film and the attached S-layer protein [55]. Thus, less than 5% of the lipid molecules of the adjacent monolayer are anchored to functional domains on the S-layer protein whereas the remaining ≥ 95% lipid molecules diffuse freely in the membrane between the pillars consisting of anchored lipid molecules (Fig.…”
Section: Semifluide Lipid Membranesmentioning
confidence: 99%